Antimicrobial, Antioxidant and Cytotoxic Activity of Silver Nanoparticles Synthesized by Leaf Extract of Erythrina suberosa (Roxb.) - Mohanta, Yugal K.; Panda, Sujogya K.; Jayabalan, Rasu; Sharma, Nanaocha; Bastia, Akshaya K.; Mohanta, Tapan K. (Frontiers in Molecular Biosciences, 2017)
In this experiment, biosynthesized silver nanoparticles (AgNPs) were synthesized using aqueous leaf extract of Erythrina suberosa (Roxb.). The biosynthesis of silver nanoparticle was continuously followed by UV-vis spectrophotometric analysis. The response of the phytoconstituents resides in E. suberusa during synthesis of stable AgNPs were analyzed by ATR- fourier-transform infrared spectroscopy. Further, the size, charge, and polydispersity nature of AgNPs were studied using dynamic light scattering spectroscopy. The morphology of the nanoparticles was determined by scanning electron microscopy. Current result shows core involvement of plant extracts containing glycosides, flavonoids, and phenolic compounds played a crucial role in the biosynthesis of AgNPs. The antimicrobial activities of silver nanoparticles were evaluated against different pathogenic bacterium and fungi. The antioxidant property was studied by radical scavenging (DPPH) assay and cytotoxic activity was evaluated against A-431 osteosarcoma cell line by MTT assay. The characteristics of the synthesized silver nanoparticles suggest their application as a potential antimicrobial and anticancer agent.